2009
DOI: 10.1016/j.jtcvs.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic segmentectomy compares favorably with thoracoscopic lobectomy for patients with small stage I lung cancer

Abstract: Thoracoscopic segmentectomy is a safe option for experienced thoracoscopic surgeons treating patients with small stage I lung cancers. No significant difference in oncologic outcome was seen between thoracoscopic segmentectomy and thoracoscopic lobectomy. Lymph node dissection could be performed as effectively during segmentectomy as lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 26 publications
7
86
0
2
Order By: Relevance
“…Currently, the specific approach remains a matter of controversy. Several series suggest that there is no difference in overall survival between lobectomies performed by VATS versus those performed by thoracotomy for clinical stage I nonsmall cell lung cancer (NSCLC) [4,5]. Morbidity appears to be lower with the VATS approach.…”
Section: Surgical Approachmentioning
confidence: 99%
“…Currently, the specific approach remains a matter of controversy. Several series suggest that there is no difference in overall survival between lobectomies performed by VATS versus those performed by thoracotomy for clinical stage I nonsmall cell lung cancer (NSCLC) [4,5]. Morbidity appears to be lower with the VATS approach.…”
Section: Surgical Approachmentioning
confidence: 99%
“…In recent years, several retrospective reports have demonstrated that segmentectomy for small-sized (diameter ≤2.0 cm) stage Ia NSCLC may be comparable to lobectomy regarding prognosis and local recurrence (3)(4)(5). However, the clinical results of wedge resection for small-sized (diameter ≤2.0 cm) stage Ia NSCLC is still under debate (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…This ability has led to many surgeons re-examining their stance on the extent of surgical resections (i.e., sublobar resections) or malignant disease processes. However, the role of parenchymal-sparing operations such as segmentectomy in the treatment of T1a lung carcinoma, is still of much debate, in part because of the retrospective nature of existing published studies (7)(8)(9). Two randomized control trials however, both of which have currently finished enrollment, will hopefully shed further light on this topic (10,11).…”
Section: Introductionmentioning
confidence: 99%